Preclinical development of novel humanised ROR1 targeting chimeric antigen receptor T cells and bispecific T-cell engagers. (23rd February 2017) - Gohil, Satyen; Paredes-Moscosso, Solange; Harrasser, Micaela; Davidoff, Andrew; Pule, Martin; Della Peruta, Marco; Nathwani, Amit
Abstract: Background: Immunotherapy with chimeric antigen receptor (CAR) T cells and bispecific T-cell engagers (BiTEs) has shown impressive efficacy against CD19+ malignancies, but translation to other tumour targets is not possible. In this regard, receptor tyrosine kinase like orphan receptor 1 (ROR1) is an attractive therapeutic target that is present on a range of haematological and solid malignancies, as well as cancer stem cells, but importantly with limited expression on normal adult tissues. Our aim, through iterative optimisation, was to generate novel humanised ROR1 single chain variable fragments (scFv) that enable efficient targeting of ROR1 on tumour cells without toxicity. Methods: 13 novel anti-ROR1 antibodies were isolated after a rat immunisation programme, of which ten bound as scFvs. These fragments were engineered into a second generation CAR structure and using lentiviral vectors generated ROR1CAR T cells, imparting ROR1-specific but MHC-independent cytotoxicity. Concurrently, ROR1 scFvs were linked with a CD3 scFv to generate BiTEs—ie, small molecules able to facilitate formation of a cytotoxic synapse between T cells and ROR1+ tumour targets. Findings: Co-culture of our ten novel CAR T-cell constructs with ROR1+ target cells demonstrated scFv dependent cytotoxicity. Two lead candidates were selected for humanisation to minimise immunogenicity, and of 50 variants constructed one in particular was able to target haematological and solid tumour cell lines (p<0·0001 for ROR1+ Raji, PCL12, and Kasumi2 cell lines) with higher interleukin 2 secretion and superior specific cytotoxicity against primary chronic lymphocytic leukaemia cells compared with competitor constructs. In addition, our optimal humanised ROR1-BiTE mediated dose-dependent cytotoxicity against cell lines at low concentrations (1 ng/mL, p<0·0001 for SKW cells at 24 h). This BiTE decreased tumour burden and increased survival in an in-vivo model of aggressive lymphoma (median survival 50 days vs 18, p=0··0339). Interpretation: Extensive evaluation and optimisation has generated ROR1 CAR and BiTE constructs that can mediate potent effector function. Although both constructs harness the immune system, their unique characteristics provide a multifaceted platform to target a broad range of malignancies, many with considerable unmet therapeutic need such as pancreatic cancer. Ongoing work aims to determine which tumour types are best targeted by BiTEs or CAR T cells and to translate these agents to the clinic. Funding: Wellcome Trust, National Institute for Health Research, NHS Blood and Transplant.